2011
DOI: 10.5005/jp-journals-10024-1044
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Dental Implant as Orthodontic Anchorage

Abstract: Aim The purpose of this three-dimensional (3D) finite element study was to investigate orthodontic loading simulation on a single endosseous implant and its surrounding osseous structure, to analyze the resultant stresses and to identify the changes in the bone adjacent to the implant following orthodontic loading. Materials and methods Two models were constructed using finite element method consisting of endosseous dental implant and the surrounding bone. In the first model, the contact between the implant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Various methods and pharmacological agents are being explored to accelerate OTM. Some of these methods include vibration, piezo puncture, corticotomy, and laser therapy, as well as the use of pharmacological agents like corticosteroids and vitamin D3 (Ambashikar et al., 2021 ; Sarmah et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various methods and pharmacological agents are being explored to accelerate OTM. Some of these methods include vibration, piezo puncture, corticotomy, and laser therapy, as well as the use of pharmacological agents like corticosteroids and vitamin D3 (Ambashikar et al., 2021 ; Sarmah et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…and pharmacological administration have attempted to accelerate the tooth movement (corticosteroids, vitamin D3, and prostaglandins). 2 Every previously employed method had drawbacks such as localized discomfort, decalcification, root resorption, and other medication side effects. 3 A surgically noninvasive procedure to hasten tooth movement is required due to the negative effects of all previously tried treatments.…”
Section: Introductionmentioning
confidence: 99%
“…FEA (finite element analysis) is a highly efficient calculating method, mainly used in analyzing static, dynamic objects and physical systems, which can also be used in the study of internal micromotion of objects. Mathur et al reported the outcome of the implant and its surrounding bone structure's orthodontic load simulated by 3D FEA [ 12 ]. Based on 3D FEA, the stress generated was analyzed and the changes in the implant's surrounding bone under orthodontic load could be identified.…”
Section: Introductionmentioning
confidence: 99%